EFISIENSI ANGGARAN DALAM PENDIDIKAN: BAGAIMANA PERSEPSI MENURUT MAHASISWA - Nugraha, Joko Tri; Pratama, Agung Danur Pratama Agung; Fatmasary, Nabila Fatmasary; Sari, Tiara Novita Sari; Manik, Arya Mangatur Manik; Asmungi, Aisyah Nuraini Asmungi (Universitas Gajah Putih, 2025)
The increasing fiscal pressures faced by educational institutions have made the issue of higher education budget efficiency an important topic. Various student perspectives on the implementation of budget efficiency policies at Tidar University prompted this research. How students see the impact of the policy on important things in the academic environment, such as scholarships, learning facilities, scientific productivity, and student organization operations, is the purpose of this study. This study used a descriptive quantitative approach. The closed questionnaire instrument was distributed to students of class 2024 of the State Administration Study Program. The results showed that the majority of students assessed the efficiency policy as bringing more negative impacts, such as a decrease in scholarships and lecturer allowances, a decrease in student activities, and an increased possibility of increased education costs. In contrast, they support transparency and accountability in budget management and efficiency directed at reducing administrative costs. This research confirms that educational efficiency should not be used to reduce budgets but should be done in a way that is fair and benefits students. These results are important for policymakers to consider as they create budget policies that are not only cost-effective but also socially equitable and support sustainable access to higher education.